THE EFFECT OF CELEBRITY ENDORSER CREDIBILITY AND BRAND IMAGE ON PURCHASE INTENTION MODERATED BY BRAND DIFFERENCE - Evi Novitasari; Nabila Kharimah Vedy; Sri Rahayu (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Social media offers many opportunities for online marketing strategies that harness the power of society, especially when they are combined with traditional approaches such as celebrity endorsements. The reach, frequency, and speed of communication on social media offer the ideal range for online marketing delivery. However, the speed of change could threaten to short-lived the effects of investing in social media marketing. The shift in behavior from offline (offline) to online ( online) in Indonesian society has opened up new opportunities in online shops . One that uses an online shop system is the cosmetic brand Oriflame, by attracting market share, one of which is through social media Facebook. For example, the cosmetic product